Disability of Gait in Stroke Survivors: Physiotherapy Clinical Use of Visual Gait Analysis in Lusaka, Zambia - Chiluba, Brian Chanda; Mwansa, Mulenga Gideon (Indonesian Journal of Disability Studies, 2019)
Stroke is one of the leading causes of severe handicap, disabling and impairing the ability to walk in 80% of all stroke survivors. Physiotherapists, all over the globe, use Observational gait analysis as a preferred method of gait assessment in their clinical practice to assess, monitor change, evaluate treatment and identify areas needing intervention in the rehabilitation of patients with gait disability. The objective of the study was to determine factors affecting the use of observational gait analysis in assessment of stroke survivors among physiotherapy practitioners at the University Teaching Hospital. The study was a cross sectional descriptive study aimed at determining the knowledge and factors affecting use of observational gait analysis and the adaption thereof as a Standard Observational Gait Assessment Tool at the University Teaching Hospital. The essential factors to the use of assessment tools were lack of guidelines and lack of knowledge on use of OGA. Also a lack of organizational support, lack of formal knowledge and no availability of assessment tools. To overcome these barriers, it is necessary to provide training of standardized assessment, and to recommend appropriate guidelines.